Proton-dependent inhibition of the cardiac sodium channel Nav1.5 by ranolazine - Sokolov, Stanislav; Peters, Colin H.; Rajamani, Sridharan; Ruben, Peter C. (Frontiers in Pharmacology, 2013)
Ranolazine is clinically approved for treatment of angina pectoris and is a potential candidate for antiarrhythmic, antiepileptic and analgesic applications. These therapeutic effects of ranolazine hinge on its ability to inhibit persistent or late Na+ currents in a variety of voltage-gated sodium channels. Extracellular acidosis, typical of ischemic events, may alter the efficiency of drug/channel interactions. In this study, we examined pH modulation of ranolazine’s interaction with the cardiac sodium channel, Nav1.5. We performed whole-cell path clamp experiments at extracellular pH 7.4 and 6.0 on Nav1.5 transiently expressed in HEK293 cell line. Consistent with previous studies, we found that ranolazine induced a stable conformational state in the cardiac sodium channel with onset/recovery kinetics and voltage-dependence resembling intrinsic slow inactivation. This interaction diminished the availability of the channels in a voltage- and use-dependent manner. Low extracellular pH impaired inactivation states leading to an increase in late Na+ currents. Ranolazine interaction with the channel was also slowed 4-5 fold. However, ranolazine restored the voltage-dependent steady-state availability profile, thereby reducing window/persistent currents at pH 6.0 in a manner comparable to pH 7.4. These results suggest that ranolazine is effective at therapeutically relevant concentrations (10µM), in acidic extracellular pH, where it compensates for impaired native slow inactivation.